Modelling Technique: Increasing posyandu cadres' knowledge regarding violence against toddlers - Malay, Mohammad Nursalim; Wahyuni, Citra (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2024)
Previous research revealed that violence against children is most often carried out by mothers with the main reason being to discipline their children and most of them have not received proper education regarding violence against children and how to raise children positively. Posyandu cadres are community agents who are an extension of government programs and have access to educate parents about violence against children. One strategy for increasing knowledge is psychoeducation which can be applied directly. Posyandu cadres regarding violence against children and emotional regulation. This research is a service-based research with a one-group pretest and posttest design with a sample size of 35 Posyandu cadres. The data analysis technique uses a paired sample t-test to determine the difference in scores before and after treatment. The research results showed that there was an increase in Posyandu cadres' knowledge regarding violence against toddlers and there was an increase in emotional regulation. These results show that implementing behaviour can increase participants' knowledge and attitudes.